2010
DOI: 10.1111/j.1600-6143.2009.02961.x
|View full text |Cite
|
Sign up to set email alerts
|

Decay Accelerating Factor is Essential for Successful Corneal Engraftment

Abstract: In contrast to immune restrictions that pertain for solid organ transplants, the tolerogenic milieu of the eye permits successful corneal transplantation without systemic immunosuppression, even across a fully MHC disparate barrier. Here we show that recipient and donor expression of decay accelerating factor (DAF or CD55), a cell surface C3/C5 convertase regulator recently shown to modulate T cell responses, is essential to sustain successful corneal engraftment. Whereas wild type (WT) corneas transplanted in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 35 publications
0
20
0
Order By: Relevance
“…Studies performed in transplant models revealed WT mice reject Daf1 -/-heart allografts with accelerated kinetics (39), and that the accelerated rejection is due to a complement-dependent augmentation of antidonor T cell immunity. Collaborative work additionally showed that donor or recipient DAF deficiency accelerates skin graft rejection (34) and overcomes the immune privilege of the eye by enhancing pathogenic T cell alloimmunity induced by normally tolerogenic corneal transplants, resulting in rapid corneal rejection (40).…”
Section: Complement and Alloreactive T Cells Complement And Effector mentioning
confidence: 99%
“…Studies performed in transplant models revealed WT mice reject Daf1 -/-heart allografts with accelerated kinetics (39), and that the accelerated rejection is due to a complement-dependent augmentation of antidonor T cell immunity. Collaborative work additionally showed that donor or recipient DAF deficiency accelerates skin graft rejection (34) and overcomes the immune privilege of the eye by enhancing pathogenic T cell alloimmunity induced by normally tolerogenic corneal transplants, resulting in rapid corneal rejection (40).…”
Section: Complement and Alloreactive T Cells Complement And Effector mentioning
confidence: 99%
“…The accelerated rejection is caused by a complement-dependent augmentation of antidonor T-cell immunity. Donor or recipient DAF deficiency accelerated skin graft rejection (23), bypassed the requirement for CD4 help in murine heart transplant rejection (119), and overcame immune privilege of the eye to cause rapid corneal transplant rejection (120). Local complement production and C5a/C5aR interactions also influence effector CD8 1 T-cell responses to allogeneic vascular endothelial cells (121) in in vitro culture systems and in vivo in response to a heart transplant (8,121) as well as T cell-dependent kidney transplant rejection in rodents (122).…”
Section: Complement and T Cell-mediated Transplant Rejectionmentioning
confidence: 99%
“…DAF deficiency also accelerates rejection and enhances T cell alloimmunity in a murine model of corneal transplantation via complement dependent mechanisms (Esposito et al 2010).…”
Section: Complement and Alloreactive T Cell Immunity Following Transpmentioning
confidence: 99%